Analysis of Expressive Speech Acts in Instagram Account Captions @Arif22_Rahmansholeh - Uswatun Khasanah Uswatun; Nuniek Setya Sukmayani (Widyantara, 2023)
This study aims to describe the expressive speech acts contained in the Instagram caption @arif22_rahmansholeh. The subject of this research is the Instagram account admin @arif22_rahmansholeh. The object of this research is the expressive speech contained in the caption of the Instagram account @arif22_rahmansholeh. This type of research is descriptive qualitative. Data collection techniques using observation and note-taking techniques. The theory used in this study is Searle's theory in Manaf (2011: 212) which classifies speech acts into five types, namely representative, directive, expressive, commissive, and declarative speech acts. Chaer (2010: 83) further explains that there are three speech acts in the study of pragmatics, namely locutionary, illocutionary, and perlocutionary speech acts. The results of this study indicate that there are 4 data forms of expressive speech acts in the Instagram account caption @arif22_rahmansholeh which consist of: expressive utterances; longing, 3; worries, 2; congratulations, 2; hope, 2.